Real-world outcomes after pembrolizumab treatment for cervical cancer: Results from a university setting - Rachel L. Furuya; Katelin Boak; Mary M. Mullen; Dong Wang; L. Stewart Massad (Gynecologic Oncology Reports)
Objective: To estimate survival among patients with cervical cancer treated with pembrolizumab, examine risk factors for poor outcomes, and assess toxicities in a real-world setting. Methods: This retrospective study included patients treated with pembrolizumab for advanced or recurrent cervical cancer at a tertiary academic center. Data were collected from patients initiating pembrolizumab treatment after May 2018 through June 2023. Overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan-Meier method. Associations between patient characteristics and OS were assessed using a Cox model. Results: Forty-four patients were included in the study. Mean age at first pembrolizumab was 51.4 years and 30 % of patients self-identified as non-White. Complete response was seen in 10 patients (23 %). Median OS was 47.5 months (95 % confidence interval (CI), 19.7 to not estimable) and median PFS was 9.1 months (95 % CI, 7.4 to 15.8). Patients with Eastern Cooperative Oncology Group Performance Status (PS) > 1 had a six-fold increased hazard of death compared to PS of 0 or 1 (p =0.0038). Five patients with a PS > 1. Four died of disease progression; one was alive at last follow-up. A total of 22 adverse events occurred, and 7 % were grade 3 or higher. Conclusion: Pembrolizumab is safe and effective for advanced and recurrent cervical cancer in a real-world population. For those with good performance, further study is needed to determine if prolonged complete responses are cures. PS should be considered when making treatment recommendations, as patients with poor PS may not experience the survival benefits shown in pivotal trials.